Multiomics analysis of human serum and animal experiments reveals the protective mechanism of Qingre Huoxue Decoction against rheumatoid arthritis - Zhang, Fuyuan; Xia, Congmin; Yang, Guang; Shang, Biyue; Huang, Guangrui; Yuan, Kai; Wang, Hesong; Gong, Xun; Jiang, Quan (Frontiers in Immunology, 2025)
ObjectiveQingre Huoxue Decoction (QRHXD) is a traditional Chinese herbal prescription widely used in clinical practice with significant therapeutic effects on RA; however, its mechanism of action remains unclear. This study aimed to investigate the efficacy and underlying mechanisms of QRHXD in treating RA through clinical research, multiomics approaches, and animal experiments.MethodsWe conducted a 24-week clinical study in which QRHXD was the primary treatment, collecting serum samples from patients before and after treatment for integrated proteomic and metabolomic analysis to identify potential therapeutic targets. Bioinformatics analysis of differentially expressed proteins (DEPs) and differential metabolites (DMs) was performed using hierarchical clustering, volcano plots, heat maps, Gene Ontology (GO), and Kyoto Encyclopaedia of Genes and Genomes (KEGG) analysis. To validate the identified therapeutic targets, we constructed a collagen-induced arthritis (CIA) mouse model.ResultsClinical research has shown that QRHXD can improve clinical symptoms and relevant indicators in RA patients, including the disease activity score-28 (DAS28), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), tender joint count (TJC), swollen joint count (SJC), visual analogue scale (VAS), patient-reported outcome (PRO), and health assessment questionnaire (HAQ). Proteomics and metabolomics analysis identified 83 DEPs and 54 DMs, including 46 upregulated and 37 downregulated proteins, as well as 11 upregulated and 43 downregulated metabolites. KEGG enrichment analysis revealed that DEPs are primarily associated with fatty acid degradation, ferroptosis, glycerolipid metabolism, and related pathways. The identified DMs are primarily associated with the AMPK signalling pathway, FoxO signalling pathway, glycolysis/gluconeogenesis, MTOR signalling pathway, and so on. GO enrichment analysis indicated that the DEPs were mainly associated with apoptotic mitochondrial changes, protein modification processes, fatty-acyl-CoA binding, and so on. Integrated proteomics and metabolomics analyses revealed a significant increase in fructose-1,6-biphosphatase 1 (FBP1) levels and a reduction in AMP-activated protein kinase (AMPK) levels in patients with RA. QRHXD inhibited FBP1 and activated AMPK signalling. Animal experiments validated the findings from proteomics and metabolomics analyses, demonstrating that QRHXD could also delay bone destruction and reduce inflammatory factor levels in CIA mice.ConclusionQRHXD may reduce the disease activity of RA, attenuate the inflammatory response, and delay bone destruction by inhibiting FBP1 and activating the AMPK signalling pathway.